Effect Of Temperature And Formic Acid Concentration On Delignification Of Leucaena Leucocephala - Nurul Athirah, Alwi; Nor Hanimah, Hamidi; Noormazlinah, Ahmad; Siti Hajar Noor, Shaarani (Universiti Malaysia Pahang, 2017)
Delignification is essential for wide range of technologies especially in paper industry and ethanol as transportation fuel.Researches have been made by thermal, mechanical, chemical and biology treatment. Recently, L. Leucocephala has been in centre of attraction for paper making industry while formic acid, a typical organosolv system has been given attention by the researchers due to effectiveness on the ability to break down and modify the lignin structure. Hence, delignification of L. Leucocephala was studied using chemical treatment with formic acid. The effect of reaction conditions including reaction temperature and formic acid concentration were investigated at atmospheric pressure for 6 hours of reaction time. Delignification percentage approximately 70–75%(v/w) with a pulp yield of 40–62%(w/w) was obtained and the optimal reaction temperature is 90oC with 90% of formic acid concentration, respectively. Therefore, temperature and formic acid concentration affected significantly on the delignification process of L. Leucocephala